The Possible Neuronal Mechanism of Acupuncture: Morphological Evidence of the Neuronal Connection between Groin A-Shi Point and Uterus. (28th February 2013) - Chen, Chun-Yen; Chern, Rey-Shyong; Liao, Ming-Huei; Chang, Yung-Hsien; Hsu, Jung-Yu C.; Chien, Chi-Hsien
Abstract : Somatovisceral reflex suggested that the somatic stimulation could affect visceral function like acupuncture which treats diseases by stimulating acupoints. The neuronal connection between somatic point and visceral organ was not clear. Uterine pain referred to the groin region has long been recognized clinically. Wesselmann, using neurogenic plasma extravasation method, showed that uterine pain was referred to the groin region through a neuronal mechanism (Wesselmann and Lai 1997). This connection could be considered through the somatovisceral reflex pathway. However, the relay center of this pathway is still not clearly identified. In the present study, bee venom was injected in the groin region to induce central Fos expression to map the sensory innervation of groin region. Pseudorabies virus (PrV), a transneuronal tracer, was injected in the uterus to identify the higher motor control of the uterus. Immunohistochemistry staining revealed the Fos expression and PrV-infected double-labeled neurons in the nucleus of solitary tract (NTS), the dorsal motor nucleus of vagus (DMX), and the paraventricular hypothalamic nucleus (PVN). These results suggest a somatoparasympathetic neuronal connection (groin-spinal dorsal horn-NTS/DMX-uterus) and a somatosympathetic neuronal connection (groin-spinal dorsal horn-NTS-PVN-uterus). These two neuronal connections could be the prerequisites to the neuronal basis of the somatovisceral reflex and also the neuronal mechanism of acupuncture.